The Metformin Paradox - Weijers, Rob N.M.; Bekedam, Dick J. (Current Diabetes Reviews, 2020)
Introduction: The Diabetes Prevention Program study results indicated that metformin therapy was not as beneficial as a lifestyle modification for delaying the development of type 2 diabetes in individuals at high risk of the disease. A key feature in the etiology of type 2 diabetes mellitus, which appears in the prediabetic phase, is a significant deficiency, compared to healthy controls, in highly flexible poly-cis-unsaturated fatty acyl chains in membrane phospholipids. This deficiency lowers membrane flexibility, which in turn, reduces the amount of all functional Class I glucose transporters, and thereby reduces glucose-mediated ATP production. This leads to an increase in essentially saturated free fatty acid (FFA) levels for fatty-acid-mediated ATP production, which will set up a vicious cycle of raising the levels of essentially saturated FFAs and lowering the level of transmembrane glucose transport. Metformin suppresses hepatic gluconeogenesis, which reduces the plasma glucose concentration. Conclusion: We hypothesize that chronic metformin treatment leads to an additional increase in essentially saturated FFAs, which causes an additional rise in membrane stiffness and hypoxia. So we propose that all these metformin-mediated activities accelerated the onset of type 2 diabetes in the participants of the metformin group in the Diabetes Prevention Program study, compared to the participants of the lifestyle-intervention group in this study. We propose that the biochemical reactions, involved in the fatty-acid-mediated ATP production, play an important part in the increase of the observed essentially saturated FFA concentrations. These statements should also extend to the metformin therapy of individuals with type 2 diabetes.
Keywords: membrane flexibility